KEPUASAN DAN LOYALITAS KONSUMEN BOLU LAPIS LEGIT SELERA RASA BANDAR LAMPUNG - Helga Kupilang Panggayu; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
Thei study aimsi toi analyze the levels of satisfaction andi loyaltyi ofi consumers toi the purchase of lapis legit sponge cake in Selera Rasa Bandar Lampung. This research was  conducted in Lapis Legit Selera Rasa, Bandari Lampungi. The research method used is a survey method. The sampling technique used was accidental samplingi. The numbers respondents was 55 costumers. The analysis method used is the i Customeri Satisfactioni Indexi (CSIi) analysisi andi thei loyaltyi pyramidi. Thei resultsi showedi thati Lapisi Legiti Selera Rasa consumers were satisfied with a high level of satisfaction (CSI = 68,85%). The consumer loyalty pyramid was at the level of liking the brand, meaning that consumers really like the brand of Lapis Legit Selera Rasa and willing to bear the transition costs.Key words: Consumer satisfaction,lapis legit cake, loyalty